A Novel Research Protocol to Evaluate Psychological Perception Using Brain Gym Exercises in Physiotherapy Students - Vaishnavi v. Siroya1 , Angela Kapoor2 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Brain Gym is an academic kinesiological program that is promoted and applied with a consistent learningpurpose that aims at enhancing performance such as memory, psychological perception and cognitiveskills. The technique requires the participant to communicate with a series of activities that help the bodyto understand the primary behaviour and learn how to coordinate the brain and entire body. Brain Gymactivities includes of 26 basic motions, which are believed to improve perception and stimulates brainhemisphere by neural re-modelling to facilitate whole brain learning. By ways of balancing both the side ofbrain, behavioral difficulties, social and intellectual burdens are expected to be reduced.Aims and Objective: This study aims to evaluate the psychological perception and decrease depression inthe undergraduate physiotherapy students.Method: Here’s a idea we suggest to check the psychological perception with brain gym interventionand the duration for practices comprises of three days a week session, duration of 25 minutes, which iscompleted in one hour. The depression anxiety stress scale (DASS 21) is used to evaluate disorder which isa valid and reliable tool. This study will be conducted in Ravi Nair Physiotherapy college, Sawangi, Meghe,Wardha. The duration of the study will be six months. The study design is of before after-type with simplerandomized sampling.Result: The data will be analysed using Student paired t test.Conculsion: The expected outcome includes the detection of stress, depression and anxiety levels whichwill be evaluated by using DASS-21. Data analysis will be done using students paired t test and conclusionof the study will be published after the results are analysed.